Aggregation, carbon, nitrogen, and natural abundance of 13C and 15N in soils under no-tillage system fertilized with injection and surface application of pig slurry for five years. Issue 3 (4th May 2021) - Francisco, Cremildo António Luís; Loss, Arcângelo; Brunetto, Gustavo; Gonzatto, Rogério; Giacomini, Sandro José; Aita, Celso; Piccolo, Marisa de Cássia; Marchezan, Carina; Scopel, Gustavo; Vidal, Ricardo Fagan
Abstract: Injection of pig slurry (PS) into soils under no-tillage system (NTS) is more efficient for improving soil chemical and physical attributes, and reducing C and N emissions, than surface applications. This study evaluated the effect of using injection and surface application of PS, compared to NPK and control treatments, on the soil aggregate, C and N contents, and isotopes 13 C and 15 N. The NTS consisted of rotations of summer (maize) and winter (black oat and wheat) grasses from 2011 to 2015. The treatments were PS injected into the soil (PSI ), PS applied on the soil surface (PSS ), chemical fertilization (NPK), and control (CTRL). The following soil properties were evaluated in the 0–5, 5–10, and 10–20 cm layers: aggregate stability (geometric mean diameter – GMD; aggregate mass distribution); total organic carbon (TOC) and total nitrogen (TN) in macroaggregates (8.0–0.25 mm), microaggregates (<0.25 mm), and bulk soil (<2.0 mm); and isotopes 13 C and 15 N in macro and microaggregates. The application of PSI improved the soil physical attributes, presenting higher GMD (0–5 cm) than the PSS, NPK, and CTRL treatments. In the 5–10 cm layer, the PSI treatments were more efficient in increasing the GMD and macroaggregate mass than the NPK. PSI also was more efficient in increasing TOC and TN when compared to PSS, and generated a higher GMD, which are protectors of these elements in the soil. The natural abundance of 15 N denoted the lower soil organic matter decomposition in the PSI treatment when compared to the PSS . The natural abundance of 13 C showed less-negative values in macroaggregates than in microaggregates, denoting that the soil management practices and crops used (grasses) affected positively the abundance of 13 C. After seven applications of PS in maize-oat-wheat rotation in NTS, the application of PSI was more efficient in improving the soil physical and chemical attributes than the application of PSS .